Recognizing taxonomic units in the fieldThe case of the crickets Oecanthus dulcisonans Gorochov 1993, and O. pellucens (Scopoli, 1763) (Orthoptera: Gryllidae): implications for their distribution and conservation in Southern Europe - Cordero, Pedro J.; Llorente, Vicenta; Cordero, Pau; Ortego, Joaquín (Zootaxa, 2009)
Recognizing taxonomic units in the field complement classical museum taxonomy. It contributes to geographical distribution assessment making possible the recognition of conservation status of conflictive and similar species. In this paper, we provide unambiguous field characters distinguishing two similar species of Oecanthus in Southern Europe: Oecanthus dulcisonans Gorochov and O. pellucens (Scopoli) that are frequently misidentified. Whereas O. dulcisonans is a southern rare species with an uncertain status and distribution, O. pellucens is common and widely distributed in the Palaearctic. Song is the easiest way to distinguish between the two species in the field being continuous in the former and with regular schemes in the latter. Further, O. dulcisonans is larger, with relatively longer inner wings protruding more apically from tegmen, and with a more slender sternum, morphological traits that are detected simply with a hand magnifier.